Kiwifruit sensitivity to boron: impact on physiological and molecular responses - Chalchisa, Gudeta; Muzahid, Abu Naim Md.; Mollah, Md Dulal Ali; Gasura, Edmore; Xie, Xiaodong; Liu, Xiaoying; Lv, Haiyan; Tian, Hua; Zhong, Caihong; Li, Dawei (Frontiers in Plant Science, 2025)
Boron (B) is an essential micronutrient critical for crop growth and productivity. However, excessive boron concentrations can impair plant development, and detoxification remains a significant challenge. Understanding genetic variability and identifying tolerance mechanisms are crucial for developing boron-resistant cultivars. This study explores the physiological and molecular responses of two Actinidia species, namely kiwifruit (A.chinensis) and kiwiberry (A.arguta), to varying levels of excess B. Under excessive B conditions, B accumulation followed the order roots< stems< leaves, with maximum concentrations of 68.6 mg/kg, 105 mg/kg, and 160.7 mg/kg in AC, and 68.2 mg/kg, 107 mg/kg, and 196.9 mg/kg in AA, respectively. B toxicity symptoms appeared in AA when B levels exceeded 50 mg/kg, leading to a 15–20% reduction in dry weight across roots, stems, and leaves. AC exhibited greater sensitivity, with a 20–30% reduction in dry biomass. Both species showed significant declines in chlorophyll a and b content under B stress, with alterations in the chlorophyll a/b ratio and increased oxidative stress. Additionally, stress-responsive genes, including 1-aminocyclopropane-1-carboxylate synthase (Actinidia10066) and xyloglucan endotransglucosylase/hydrolase (Actinidia11948), were downregulated in response to B stress, suggesting potential disruptions in growth and development. These findings provide valuable insights into the differential physiological and molecular responses to excess boron in Actinidia species, laying a foundation for functional genomics research and the development of boron-tolerant kiwifruit cultivars.